Microwave selective heating for size effect of water droplet in W/O emulsion with sorbitan fatty acid monostearate surfactant. (September 2015) - Sumi, Takuya; Horikoshi, Satoshi
Abstract: A stable water/oil (W/O) emulsion was prepared by adjustment with sorbitan fatty acid monoester surfactants. The prepared W/O emulsion was stable for 60 min in the atmosphere; however, the formation of non-uniform water droplets in the height of the emulsion in the quartz tube reactor were observed by the backscattering measurements with an infrared laser at 850 nm. The increase of temperature under microwave irradiation was influenced sensitively by the position of those water droplets. Those results were caused from the size and concentration of water droplets in the W/O emulsion. On the other hand, selective heating of the water droplets caused heating of the entire W/O emulsion, although the temperature difference between the water droplets and the oil phase was 20 °C. Graphical abstract: The feature of a selective heating phenomenon in a W/O emulsion under microwave irradiation was investigated both practically and theoretically. Temperature profiles of emulsions stabilized with different sorbitan fatty acid monoester surfactants indicated that a smaller size distribution of water droplets leads to a higher heating rate. Moreover, computational studies suggested that water droplets in oil are 20 °C higher than the organic phase. Highlights: The microscopic heating features of microwaves in a W/O emulsion were examined. The microwave heating behaviors reflected the properties of water droplets. The heat convection process in a W/O emulsion was studied by a theoretical approach.